A potential impact of Helicobacter pylori-related galectin-3 in neurodegeneration. (February 2018) - Boziki, Marina; Polyzos, Stergios A.; Deretzi, Georgia; Kazakos, Evangelos; Katsinelos, Panagiotis; Doulberis, Michael; Kotronis, Georgios; Giartza-Taxidou, Evaggelia; Laskaridis, Leonidas; Tzivras, Dimitri; Vardaka, Elisabeth; Kountouras, Constantinos; et al.
Abstract: Neurodegeneration represents a component of the central nervous system (CNS) diseases pathogenesis, either as a disability primary source in the frame of prototype neurodegenerative disorders, or as a secondary effect, following inflammation, hypoxia or neurotoxicity. Galectins are members of the lectin superfamily, a group of endogenous glycan-binding proteins, able to interact with glycosylated receptors expressed by several immune cell types. Glycan-lectin interactions play critical roles in the living systems by involving and mediating a variety of biologically important normal and pathological processes, including cell-cell signaling shaping cell communication, proliferation and migration, immune responses and fertilization, host-pathogen interactions and diseases such as neurodegenerative disorders and tumors. This review focuses in the role of Galectin-3 in shaping responses of the immune system against microbial agents, and concretely, Helicobacter pylori (Hp), thereby potentiating effect of the microbe in areas distant from the ordinary site of colonization, like the CNS. We hereby postulate that gastrointestinal Hp alterations in terms of immune cell functional phenotype, cytokine and chemokine secretion, may trigger systemic responses, thereby conferring implications for remote processes susceptible in immunity disequilibrium, namely, the CNS inflammation and/or neurodegeneration. Graphical abstract: Highlights: Galectins interact with glycosylated receptors expressed by epithelial/immune cells. Hp antigens/epitopes serve as immunogens locally and systematically. Hp infection induces Gal-3 expression by gastric epithelium. Gal-3 & Hp infection may pleitropically contribute to neurodegenerative pathologies. Mechanisms include: BBB breakdown, macrophage defects, IL-8, toxic agents and MetS.